Серебряная лодка: стихи и поэмы : перевод с удмуртского / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1989)
Экземпляры: ХР (20171004) / Инвентарный номер: 25909 / Цена: 1 / Авт.знак: Б 18 / ГРНТИ: 17 / ББК: 84(2Рос.Удм)^VLBC/RL